Native casein micelles as nanocarriers for β‐carotene: pH‐and temperature‐induced opening of the micellar structure. (3rd April 2017) - Moeller, Henrike; Martin, Dierk; Schrader, Katrin; Hoffmann, Wolfgang; Lorenzen, Peter Chr.
Summary: To apply native casein micelles (CM) as nanocarriers for lipophilic substances in non‐ or low‐fat food products, they have to be conditioned before loading. In this study, an experimental set‐up for the production and loading of CM was developed. Microfiltration was used to separate CM from skimmed milk. To identify optimal loading conditions temperatures (2, 20, 40 °C), pH values (6.8 and 5.5) and holding times (5, 15, 30, 60 min) were varied. The release of calcium, phosphate and protein from the micellar phase as well as static light scattering and transmission electron microscopy showed that CM were optimally primed at 2 °C and a pH of 5.5 for 5 min. Therefore, loading with β‐carotene was performed under those conditions. After the back‐extraction of β‐carotene, the photometrical analyses revealed total recovery rates of >79% whereby 94% of it was associated with the native CM. Abstract : Obtaining and conditioning of native casein micelles (CM) and subsequent loading with β‐carotene applying three different loading‐concentrations (C1–C3). β‐carotene was back‐extracted and its recovery rate as well as its distribution determined.